SPECIAL RAW MATERIAL ZONES IN RECLAIMED SOILS OF THE LVIV REGION - Pryshchepa, Alla; Zolotarova, I. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Cultivation of organic agricultural products prompted the select special zones for raw materials. For this the studied sanitary hygienic agrochemical indicators and indicators of soil sustainability reclaimed land of the Lviv region. The main influence on the formation of special zones for raw materials has the location of industry, chemicalization fields and nutrient content.